Africa and the taxation of permanent establishments: Is the definition of "permanent establishment" as used in the double tax agreements of selected 'fishing rich' African countries sufficient to protect the taxing rights on those diminishing natural resources? - Strandvik, Ulrik Bernhard (Department of Commercial Law, 2015)
Includes bibliographical references (leaves 115-119).